Host genus and rainfall drive the population dynamics of a vascular epiphyte. Issue 11 (17th November 2016) - Ticktin, Tamara; Mondragón, Demetria; Gaoue, Orou G.
Abstract: Vascular epiphytes constitute up to 25% of tropical plant diversity and play an important role in providing food, water, and shelter to many organisms. However, the factors that drive their population dynamics, including the influence of their host plants (phorophytes) and of climatic factors, are still poorly understood. We provide the first test of whether host tree genus can affect population dynamics of an epiphytic species, and assess the interactive effects of host tree and rainfall. We carried out a five‐year study of the demography of >1000 plants of the endemic bromeliad, Tillandsia macdougallii L. B. Sm, growing on pine and oak trees in a Mexican montane forest. We tested for differences in vital rates and used integral projection models to test whether these scaled up to differences in long‐term population growth rates between the two host genera and as a function of rainfall. T. macdougallii survival and growth were higher on pines than on oaks for larger plants but not for seedlings. The probability of producing capsules was higher for T. macdougallii on oaks than on pines. Increasing dry season rainfall was significantly correlated with increased survival of individuals, but not of ramets, growing on both oaks and pines. The probability of clonal reproduction increased significantly with increasing dry season rainfall for T. macdougallii growing on oaks, but not on pines. Projected long‐term population growth rates, λ, for T. macdougallii on pines were higher than on oaks. Lambda increased steeply as a function of dry season rainfall for T. macdougallii populations on both host tree genera, but the increase was steeper for populations on oaks, likely because the former are deciduous. Our results show that host tree genus can affect the long‐term dynamics of epiphyte populations and suggest that these effects may depend on rainfall. The high sensitivity of this species to changes in dry season rainfall suggests that a better understanding of how rainfall may drive vascular epiphyte populations will be critical for understanding the effects of climate change on species persistence.